GS305+04-26: revisiting the interstellar medium around the Centaurus OB1 stellar association - Corti, Mariela Alejandra (2012)
Context. Massive stars deeply modify their surrounding interstellar medium (ISM) via their high throughput of ionizing photons and their strong stellar winds. In this way, they may create large expanding structures of neutral gas. Aims. We study a new large neutral hydrogen (Hi) shell, labelled GS305+04-26, and its relationship with the OB association Cen OB1. Methods. To carry out this study, we have used a multi-wavelength approach. We analyse both Hi line data retrieved from the Leiden-Argentina-Bonn (LAB) survey and new spectroscopic optical observations obtained at CASLEO, as well as make use of proper motion databases available from CDS. Results. The analysis of the Hi data reveals a large expanding structure GS305+04-26 centred at (l,b) = (305°, + 4°) in the velocity range from −33 to −17 km s-1. Based on its central velocity of −26 km s-1 and using standard galactic rotation models, a distance of 2.5 ± 0.9 kpc is inferred. This structure, elliptical in shape, has a major and minor axis of 440 and 270 pc, respectively. Its expansion velocity, total gaseous mass, and kinetic energy are ~8 km s-1, (2.4 ± 0.5) × 105 M⊙, and (1.6 ± 0.4) × 1050 erg, respectively. Several stars of the OB-association Cen OB1 are seen projected onto, and within, the boundaries of GS305+04-26. Based on an analysis of proper motions, new members of Cen OB1 are identified. The mechanical energy injected by these stars could have been the origin of this Hi structure.